Acute toxicity test of avocado (Persea americana) oil in mice - Bhila, Aisya Salsa; Andriyanto, Andriyanto; Prasetyo, Bayu Febram (Current Biomedicine, 2024)
Background: Avocado (Persea americana) fruit has a high oil content, so it is widely used in the pharmaceutical and cosmetic industries. Objective: This study aims to determine the toxicity of avocado oil in mice using the lethal dose (LD50) method so that it can be used as a reference for further testing. Methods: This study used a total of 20 DDY strain female mice, which were divided into 5 groups: one control group and four treatment groups that were fed with avocado oil with 5, 10, 15, and 20 g/kg BW doses orally. The mortalities of experimental mice were observed for 14 days after treatment. Other parameters observed in this study were physiological response, body weight, absolute organ weight, and relative organ weight. Results: There was a change in behavior, and the obtained LD50 value was 25.4 g/kg BW. Observation of physiological responses, body weight, absolute organ weights, and relative organ weights showed no significant differences. Conclusion: It was concluded that avocado oil is considered relatively harmless and safe to use.